2014
DOI: 10.1111/bju.12523
|View full text |Cite
|
Sign up to set email alerts
|

Varicocele decreases epididymal neutral α‐glucosidase and is associated with alteration of nuclear DNA and plasma membrane in spermatozoa

Abstract: Objective• To assess the relationship between a marker of epididymal function and both the fragmentation of the sperm nucleus and the integrity and maturity of the sperm membrane in patients with or without varicocele. Patients and Methods• Semen samples were obtained from men with varicocele grades II and III (n = 60) and from a control group with zoospermia defined as normal (n = 30). • Samples were evaluated by a spermiogram, a hypoosmotic swelling test (HOST), neutral α-glucosidase (NAG) enzyme activity, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 49 publications
(60 reference statements)
2
41
0
Order By: Relevance
“…Selenium in seminal plasma also correlates with good spermatozoa concentrations, motility, and morphology, and that decrease in selenium concentration, in varicocele patients, was associated with detriment of seminal parameters 17 , which is comparable to our results of decreasing sperm membrane integrity in patients with lower selenium concentration, even though seminal parameters remain normal. Compared to patients with varicocele grades II and III, and the control group with no varicocele 18 , it is indicative that HOS test results and sperm quality were significantly lower in the varicocele group of patients. This data suggests that a reduction of fertilization capacity in men during varicocele can result from damage to both the testis and the epididymis, but unlike our study, they did not include selenium and carnitine as parameters of epididymal function and they included patients with grade III varicocele, which is opposite to our study with low grade varicocele participants.…”
Section: Discussionmentioning
confidence: 83%
“…Selenium in seminal plasma also correlates with good spermatozoa concentrations, motility, and morphology, and that decrease in selenium concentration, in varicocele patients, was associated with detriment of seminal parameters 17 , which is comparable to our results of decreasing sperm membrane integrity in patients with lower selenium concentration, even though seminal parameters remain normal. Compared to patients with varicocele grades II and III, and the control group with no varicocele 18 , it is indicative that HOS test results and sperm quality were significantly lower in the varicocele group of patients. This data suggests that a reduction of fertilization capacity in men during varicocele can result from damage to both the testis and the epididymis, but unlike our study, they did not include selenium and carnitine as parameters of epididymal function and they included patients with grade III varicocele, which is opposite to our study with low grade varicocele participants.…”
Section: Discussionmentioning
confidence: 83%
“…Widely received theories as to the anatomical cause include the failure of the antireflux valve where the internal spermatic vein joins the left renal vein causes reflux and retrograde flow in the testicular vein, the ‘Nutcracker effect’, and the left lateral spermatic vein is perpendicularly injected into the left renal vein to cause hydrostatic pressure in the pampiniform venous plexus. The etiology of varicocele is multifactorial, and pathogenic mechanisms of varicocele remain unclear (Alsaikhan et al ., ); however, the varicocele can lead to increased venous pressure (Eisenberg & Lipshultz, ), elevated testicular temperature (Garolla et al ., ), oxidative stress (Gholirad et al ., ), hypoxia (Hu et al ., ), and ultimately to testicular injury (Vivas‐Acevedo et al ., ). It has been confirmed that operation includes surgical varicocelectomy, microsurgical varicocelectomy, laparoscopic varicocelectomy, and percutaneous embolization can relieve the clinical symptoms to some extent about testicular pain (Han et al ., ) and improve the quality of spermatozoa including the total sperm count, sperm concentration, sperm activity, and increase the rate of pregnancy (Kim et al ., ; Wang et al ., ; Yuan et al ., ), but postoperative recurrent or persistent varicoceles are common complications; therefore, studying on the pathogenesis is needed more to reveal a deeper cause.…”
Section: Discussionmentioning
confidence: 97%
“…2 Spermatogenesis is a temperature-dependent process, which scrotal temperature is kept lower than 2°C to 8°C of the core body temperature and regulated by a specialized blood supply. [13][14][15][16] The epididymis is the main source of carnitine in human seminal plasma. [3][4][5][6] Previous studies on sperm parameters, sperm apoptosis, oxidative stress, and molecular mechanisms have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] The epididymis produces neutral α-glucosidase and carnitine which have been used to evaluate epididymal function and/or obstruction in the epididymis. [13][14][15][16] The epididymis is the main source of carnitine in human seminal plasma. [17][18][19][20][21] Although there are many reports for the biochemical evaluation of the seminal activity of carnitine as an important parameter to test epididymal function and patency, to the present, the impact of the SH on seminal carnitine has not been published.…”
Section: Introductionmentioning
confidence: 99%